Calcium and Cholecalciferol Levels in Late-Phase Laying Hens: Effects on Productive Traits, Egg Quality, Blood Biochemistry, and Immune Responses - Attia, Youssef A.; Al-Harthi, Mohammed A.; Abo El-Maaty, Hayam M. (Frontiers in Veterinary Science, 2020)
Productive traits and immunity in laying hens decrease sharply during the late phase of laying due to ageing, which negatively affects the metabolism and hormonal status of the animals. The influence of Ca levels (3.5, 4.0, and 4.5%) and/or cholecalciferol [Vitamin D3, (VD3)] supplementation (800, 1000, and 1200 IU/kg diet) on performance, egg quality, blood biochemistry and immunity of brown egg layers was investigated. Three hundred and sixty H&N Brown egg layers (60 weeks old) were allocated at random into nine nutritional treatments of five replications (cages) of eight hens each. The addition of VD3 at 1000 and 1200 IU to 3.5 and 4% Ca diets increased the rate of laying, egg mass, and feed conversion ratio. Besides, VD3 at 800 and 1200 IU to 3.5% Ca level diets enhanced the Haugh unit score, eggshell quality, and tibia ash. The improved eggshell quality was confirmed by electron microscopy. Increasing the Ca from 3.5 to 4 and 4.5% and increasing VD3 from 800 to 1000 or 1200 IU significantly and similarly increased serum total protein and globulin, and 1000 IU increased serum albumin compared to 800 IU. Increasing Ca level increased IgA linearly, and 4 and 4.5% Ca levels similarly increased IgG and α-2 globulin compared to the 3.5% Ca diet. VD3 at 1200 IU to the 4% Ca diet significantly increased γ-globulin compared to 1000 IU, but decreased β-globulin. Increasing the Ca to 4% significantly reduced serum triglycerides, and the very low-density lipoprotein and the triglyceride/high-density lipoprotein ratio were both decreased with 4, and 4.5% Ca level diets. Increasing the Ca level caused a stepwise increase in catalase, which was markedly increased with VD3 at 1200 IU. Plasma estrogen was increased considerably with VD3 supplementation at 3.5% Ca. In conclusion, increasing Ca levels in laying hens diets to 4% during the late production phase could be a useful tool to improve laying performance, eggshell quality, Haugh unit score, and physiological and immunological status. Besides, VD3 at 1000 IU/kg diet to 3.5% Ca improved performance of hens fed 3.5% Ca, showing that the potential impact of VD3 depends on Ca concentrations.